Analysis of the Utilization of QRIS on the Consumptive Behavior of the Academic Community, Faculty of Economics and Business, Universitas Nusantara PGRI Kediri - Alifia, Irsa Nabila (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This research attempts to investigate the implication of QRIS as a digital payment method by examining three key indicators: perception of convenience, perceived usefulness, and risk, on the consumptive behavior of the academic community at the department of Economics and Business of Universitas Nusantara PGRI Kediri. Design/Methode/Research Design: This study applies a statistical technique for causality analysis with a causal study design to examine the cause-and-effect relationship between perceptions of convenience, benefits, and risks of using QRIS on the consumptive behavior of the academic community at Universitas Nusantara PGRI Kediri. Data was collected using a questionnaire based on a Likert scale, which was distributed to 327 respondents as the research sample. The sample gathering technique was accidental selection, and the assessment of accuracy and consistency, classical assumption tests, linear multivariate modeling, and statistical hypothesis analysis using mean comparison test and Anova test. This approach aims to provide objective and measurable insights into the impact of digital payment technology on consumption behavior within the academic setting. Research Finding: The observation regarding this study show that QRIS usage strongly influences the consumptive behavior of the academic community at Universitas Nusantara PGRI Kediri. This effect is mainly driven by perceptions of convenience, benefits, and risks associated with its use. The data suggests that as QRIS becomes easier and more beneficial to use, along with perceived risks, consumptive behaviors such as impulse buying and unplanned spending also tend to increase. These results align with previous studies, further supporting the idea that digital payment technology not only simplifies transactions but also shapes consumption habits, particularly in academic settings. Theoretical contribution/Originality: This study contributes theoretically by providing insights into consumer behavior, particularly in the context of digital payments like QRIS. The findings reinforce theories regarding the impact of perceived benefits, ease of use, and risk on consumptive behavior. Additionally, this research can serve as a reference for developing theories on how financial technology influences consumptive lifestyles, especially among students who actively use digital technology. This also creates opportunities for further exploration of the relationship between digital innovation and individual economic behavior. Practitionel/Policy implication: This study provides practical implications for financial practitioners and policymakers to pay more attention to the impact of QRIS use on consumptive behavior, especially among students. Financial institutions and digital payment service providers can develop educational programs on the wiser use of QRIS, in order to reduce the risk of impulse purchases. In addition, the campus can provide financial literacy to the academic community so that they better understand personal financial management in the digital era. This policy is important to create a healthier and more responsible financial ecosystem in the academic environment. Research limitations: This research has several limitations that need to be considered, such as the focus of the research is only on the academic community of the Economics and Business Department of Universitas Nusantara PGRI Kediri, therefore the result may not be generalized to a wider population.